2006
DOI: 10.1002/nau.20349
|View full text |Cite
|
Sign up to set email alerts
|

Urinary flow disturbance as an early sign of autonomic neuropathy in diabetic children and adolescents

Abstract: The decreased acceleration of detrusor muscle contraction may be interpreted as an early sign of autonomic neuropathy in children and adolescent with type 1 diabetes, even in patients without CAD. Clinicians may be able to determine autonomic neuropathy by using uroflowmetry that is easy to perform, sensitive, reproducible, and needs only a child's minimal cooperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…First, children who are overweight tend to consume an unhealthy diet that may overwhelm functional bladder capacity and result in nocturnal diuresis. 14,26,36 Second, hyperglycemia has been suggested as a possible cause for secondary enuresis in obese youth, 17,18 though in our study the vast majority of the patients reported primary enuresis. Third, as mentioned above, both enuresis and obesity cooccur with psychological distress; 5,6,14,15,19,22,[27][28][29][30][31] enuresis increases psychological distress in children creating a vicious cycle that perpetuates enuresis, obesity and distress.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…First, children who are overweight tend to consume an unhealthy diet that may overwhelm functional bladder capacity and result in nocturnal diuresis. 14,26,36 Second, hyperglycemia has been suggested as a possible cause for secondary enuresis in obese youth, 17,18 though in our study the vast majority of the patients reported primary enuresis. Third, as mentioned above, both enuresis and obesity cooccur with psychological distress; 5,6,14,15,19,22,[27][28][29][30][31] enuresis increases psychological distress in children creating a vicious cycle that perpetuates enuresis, obesity and distress.…”
Section: Discussionmentioning
confidence: 50%
“…9,13-16 Type 2 diabetes mellitus is more prevalent in obese youth than in normal-weight youth; 9,15 enuresis constitutes one of the typical signs of type 2 diabetes mellitus. 17,18 Increased prevalence of ADHD is observed among enuretic children, as well as increased prevalence of enuresis among children suffering from ADHD. 5,[19][20][21][22][23][24] In addition, several authors have observed an association between obesity and voiding dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Using simple and noninvasive uroflowmetry, we found that men with T2DM and aged <45 years had a larger bladder capacity but similar Q max to controls. Szabo et al [15] reported similar findings, that children with T2DM and adolescents with cardiovascular autonomic dysfunction had a larger voided volume, but similar Q max and no measurable PVR. In animal studies, DM and associated diuresis were correlated with increased bladder capacity and a change in the mechanical properties of bladder wall, compared with controls [16].…”
Section: Discussionmentioning
confidence: 64%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] years. Compared with controls, men with T2DM had a significantly mean ( SD ) higher IPSS, of 6.1 (5.8) vs 4.1 (4.6) ( P < 0.001), an increased of odds ratio (95% confidence interval) of having moderate to severe LUTS of 1.78 (1.12-2.84) ( P = 0.01), greater voiding volume of 376 (177) vs 326 (102) mL ( P = 0.04), a worse IIEF-5 score of 17.3 (6.4) vs 20.0 (3.8) ( P < 0.001), an increased of odds ratio of having moderate to severe ED of 3.5 (2.1-5.8) ( P < 0.001) but a similar maximum flow rate and postvoid residual.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation